2003
DOI: 10.1108/09600030310471970
|View full text |Cite
|
Sign up to set email alerts
|

Collaborative networking in a multi‐stage industrial channel

Abstract: The argument of the paper is that the global competitive strength of leading Japanese products lies not only in their efficient supply systems but also in systems of multi‐stage vertical networks. The study explores an example of such a network throughout a multi‐stage industrial complex in the home electronics industry in Japan. Members of this network are an assembly firm, a plastic parts supplier, and a mold processor. The paper concludes that for such collaborations to succeed in creating products of globa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…Nielson (1998) suggested that closeness between partners is positively associated with a commitment to the relationship. Fujimoto (2003) also found that an embedded tie encourages each party to make considerable commitments. Thus:…”
Section: Embedded Ties and Competitive Advantagementioning
confidence: 94%
“…Nielson (1998) suggested that closeness between partners is positively associated with a commitment to the relationship. Fujimoto (2003) also found that an embedded tie encourages each party to make considerable commitments. Thus:…”
Section: Embedded Ties and Competitive Advantagementioning
confidence: 94%
“…The importance of relationship of dependent and independent, external and internal participants in a CMN has been described by several researchers. Firstly, it is need to define participants relationship in a collaboration network [24,25,29,30,31,32]. Then trust and commitment in this relationship are required to link their activities and resource ties and to describe interdependency of internal and external participants, determine performance network and identify additional opportunities for joint project [8,11,25,33,34].…”
Section: Relationship Of Dependent and Independent Participantsmentioning
confidence: 99%
“…This also can be used to gain competitive advantages in cost savings, technological innovation, shorter lead times, joint marketing program and shortened response time [35] under the competitive pressures. This is important in determining long term relationship [26,31,36]. This long term relationship need strong business interdependencies which is relies on information exchange, collaborative planning and operation management and business rules of the game [11,30,35].…”
Section: Relationship Of Dependent and Independent Participantsmentioning
confidence: 99%
“…Location is a key factor for all the transport operators [2,[4][5][6][7]. Reduction of the delivery time to the final destination or to the following passage of the logistics/transport chain is one of the elements that could make an important difference when a transport operator is being chosen.…”
Section: Introductionmentioning
confidence: 99%